Optimalisasi Penggunaan Canva sebagai Media Pembelajaran Interaktif dan Menyenangkan pada Mahasiswa PAI Universitas Islam - Herwati; Mahfudz Sulaiman; Lathifah Lailatassaidah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
Advances in digital technology have opened up opportunities for educators to utilize a variety of more creative and innovative learning media. One approach that can be employed is the use of the Canva app, which enables users to create various types of visual designs such as presentations, info graphics, and learning materials with a more engaging appearance. This study aims to determine how the Canva app is used as a learning medium and its role in creating interactive learning experiences for students in the Islamic Education Program at Zainul Hasan Genggong Islamic University. This study employs a descriptive qualitative approach by collecting data through interviews with the students. The Research shows that most students use Canva to create a variety of materials, including presentations, concept maps, and visual aids used in class. Delivering material through Canva is considered to help students create more engaging presentations, foster creativity, and make the learning process more interactive and less monotonous. Media created using Canva can also boost students’ confidence when presenting material in front of the class. However, several obstacles were identified: some students still struggle to understand and utilize the various features available in Canva, resulting in suboptimal use of the platform. It can be concluded that Canva plays a significant role as a learning tool that can support more interactive and engaging learning experiences, although students still need to improve their understanding of how to make the most of its feature.